Compulsory Immunization Protects Against Infection: What Law and Society Can Do - Maxwell J. Mehlman; Michael M. Lederman (Case Western Reserve University, 2020)
Since their broad implementation, immunizations have decreased morbidity and mortality due to a number of serious infectious diseases. In recent years, exaggerated concerns about the safety of immunizations have resulted in decreased immunization coverage in many regions and epidemic outbreaks of serious transmissible diseases - most particularly measles. This commentary reviews the legal justification for compulsory immunization and the ethical justification for civil incentives to assure compliance with immunization practices.